2019
DOI: 10.1007/s10552-018-1121-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in race, molecular and tumor characteristics among women diagnosed with invasive ductal and lobular breast carcinomas

Abstract: Background The dominant invasive breast cancer histologic subtype, ductal carcinoma, shows intrinsic subtype diversity. However, lobular breast cancers are predominantly Luminal A. Both histologic subtypes show distinct relationships with patient and tumor characteristics, but it is unclear if these associations remain after accounting for intrinsic subtype. Methods Generalized linear models were used to estimate relative frequency differences (RFDs) and 95% confidence intervals (95% CIs) for the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 52 publications
(66 reference statements)
8
25
0
Order By: Relevance
“…[32] . However, Williams and colleagues reported that malignant axillary deposit increase in ductal than in lobular and mixed carcinoma [33] In this study statistical analysis reported that tumor grade 2 had positive metastatic axillary lymph node more than tumor grad 3. Chisthi et al [13] reported that, grade 2 tumors cells tend to be slow growing which occur at invasive tumor growth cycle is longer and this increase opportunity of lymphovascular invasion.…”
Section: Chakraborty Et Al Reported Results Of 426 Patients With Bcmentioning
confidence: 61%
“…[32] . However, Williams and colleagues reported that malignant axillary deposit increase in ductal than in lobular and mixed carcinoma [33] In this study statistical analysis reported that tumor grade 2 had positive metastatic axillary lymph node more than tumor grad 3. Chisthi et al [13] reported that, grade 2 tumors cells tend to be slow growing which occur at invasive tumor growth cycle is longer and this increase opportunity of lymphovascular invasion.…”
Section: Chakraborty Et Al Reported Results Of 426 Patients With Bcmentioning
confidence: 61%
“…The percentage of cells stained for antibodies was verified by a binocular microscope (Zeiss KF2 binocular, Germany). The positivity of HER2 was defined when the membrane/membrane plus cytoplasmic staining by antibody (A0485, 1/200; Dako Denmark A/S) classified as the weak or greater intensity at ≥10% of tumor cells 39 . The antibody used for ER staining was Clone ID5; Dako Denmark A/S (Glostrup, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of stained cells by the antibodies was examined using a binocular microscope (Zeiss KF2 binocular, Germany). HER2 positivity was determined when the membrane/membrane plus cytoplasm stained by antibody (A0485, 1/200; Dako Denmark A/S) accounted for ≥ 10% of tumor cells (28). The Clone ID5 (Dako Denmark A/S) antibody (Glostrup, Denmark) was applied to detect the frequency of cells with ER positivity.…”
Section: Histopathological Datamentioning
confidence: 99%